Single-Cell Transcriptomics of Proliferative Phase Endometrium: Systems Analysis of Cell–Cell Communication Network Using CellChat - Fang, Zishui; Tian, Yao; Sui, Cong; Guo, Yaxin; Hu, Xinyao; Lai, Youhua; Liao, Zhiqi; Li, Jie; Feng, Guihai; Jin, Lei; Qian, Kun (Frontiers in Cell and Developmental Biology, 2022)
The endometrium thickness increases by which endometrial angiogenesis occurs in parallel with rapid growth of endometrium during the proliferative phase，which is orchestrated by complex cell-cell interactions and cytokine network. However, the intercellular communication has not been fully delineated. In the present work, we studied the cell-cell interactome among cells of human proliferative phase endometrium using single-cell transcriptomics. The transcriptomes of 33240 primary endometrial cells were profiled at single-cell resolution. CellChat was used to infer the cell-cell interactome by assessing the gene expression of receptor-ligand pairs across cell types. In total, 9 cell types and 88 functionally related signaling pathways were found. Among them, growth factors and angiogenic factors signaling pathways including EGF, FGF, IGF, PDGF, TGFb, VEGF, ANGPT, ANGPTL which are highly associated with endometrial growth，were further analyzed and verified. The results showed stromal cells and proliferating stromal cells represented cell-cell interaction hubs with a large number of EGF, PDGF incoming signals and FGF outgoing signals. Endothelial cells exhibited cell-cell interaction hubs with plenty of VEGF, TGFb incoming signals and ANGPT outgoing signals. Unciliated epithelial cells, ciliated epithelial cells and macrophages exhibited cell-cell interaction hubs with substantial EGF outgoing signals. Ciliated epithelial cells represented cell-cell interaction hubs with large of IGF and TGFb incoming signals. Smooth muscle cells represented lots of PDGF incoming signals and ANGPT，ANGPTL outgoing signals. This study deconvoluted complex intercellular communications at single-cell level and predicted meaningful biological discoveries, which deepened the understanding of communications among endometrial cells.